A mixed-method study of quality, availability and timeliness of non-communicable disease (NCD) related data and its link to NCD prevention: Perceptions of health care workers in Ethiopia. Issue 3 (September 2019) - Kassa, Melkamu Dugassa; Grace, Jeanne Martin
Background: Three-quarters of non-communicable disease (NCD) mortality occurs in low- and middle-income countries. However, in most developing countries, quality and reliable data on morbidity, mortality and risk factors for NCD to predict its burden and prevalence are less well understood and availability of these data is limited. To better inform policymakers and improve healthcare systems in developing countries, it is also important that these factors be understood within the context of the particular country in question. Objective: The aim of this study is to further inform practitioners in Ethiopia about the availability and status of NCD information within the Ethiopian healthcare system. Method: A mixed method research design was used with data collected from 13 public referral hospitals in Ethiopia. In phase 1 quantitative data were collected from 312 health professionals (99 physicians; 213 nurses) using a cross-sectional survey. In phase 2, qualitative data were collected using: interviews ( n = 13 physician hospital managers); and one focus group ( n = 6 national health bureau officers). Results: Results highlighted the lack of NCD morbidity, mortality and risk factor data, periodic evaluation of NCD data and standardised protocols for NCD data collection in hospitals. The study also identified similar discrepancies in the availability of NCD data and standardised protocols for NCD data collection among the regions of Ethiopia. Conclusion: This study highlighted important deficiencies in NCD data and standardised protocols for data collection in the Ethiopian healthcare system. These deficiencies were also observed among regions of Ethiopia, indicating the need to strengthen both the healthcare system and health information systems to improve evidence-based decision-making. Implications: Identifying the status of NCD data in the Ethiopian healthcare system could assist policymakers, healthcare organisations, healthcare providers and health beneficiaries to reform and strengthen the existing healthcare system.